Noma: Experiences of Survivors, Opinion Leaders and Healthcare Professionals in Burkina Faso - Kagoné, Moubassira; Mpinga, Emmanuel Kabengele; Dupuis, Marc; Marie-Solène Adamou Moussa-Pham; Srour, Margaret Leila; Maïna Sani Malam Grema; Ngoyi-Bukonda Zacharie; Baratti-Mayer, Denise (Tropical Medicine and Infectious Disease, 2022)
The scientific literature on noma (Cancrum Oris) has clearly increased in recent decades, but there seems to have been limited analysis of issues around the psycho-social impacts of this disease. Even when these issues have been addressed, the focus has tended to be on patient experiences, whereas the community dimension of the disease and the role of healthcare professionals and community leaders in mitigating these impacts remain largely unexplored. A study in the form of semi-directed interviews with 20 noma survivors and 10 healthcare professionals and community leaders was conducted between January and March 2021 in Burkina Faso with the aim of describing the experiences of noma survivors, generating knowledge about living with the burden of the disease and understanding the attitudes of community leaders towards the disease. The results reveal that noma is a disease that affects economically vulnerable populations and leads to extreme household poverty. As far as treatment is concerned, patients tend to turn to practitioners of both traditional and modern medicine. Within communities, noma survivors face discrimination and stigma. The study highlighted a lack of information and knowledge about noma. However, surgical operations lead to patient satisfaction and these remain one of the coping strategies used to tackle the stigma and discrimination. The recommendations set out in this article are aimed firstly at stepping up research into the psycho-social impacts of noma, and secondly at considering these impacts in regional programmes and national plans to combat the disease.